Impact of Green Construction Procurement on Achieving Sustainable Economic Growth Influencing Green Logistic Services Management and Innovation Practices - Sandra Marcelline, Tsimisaraka Raymondo; Chengang, Ye; Ralison Ny Avotra, Andrianarivo Andriandafiarisoa; Hussain, Zahid; Zonia, Josoa Eric; Nawaz, Ahsan (Frontiers in Environmental Science, 2022)
Green construction procurement is a part of the sustainable development goals (SDGs) that influence economic growth on a strategic level. Adopting green technologies and practices has no longer been an option but a well-worth route for gaining a competitive advantage in the construction sector. The emergent concepts of green procurement and sustainability have raised the need to measure the financial performances in terms of supply chain practices. Green procurement is now gaining importance in the construction industry and supply chain practices for a safer tomorrow. The study aimed to investigate the impact of construction procurement on green logistic services, innovation practices and their subsequent role in gaining sustainable economic development goals (SDGs). The population frame for this study was the project teams ( engineers and project managers) of construction companies in China. The sampling design followed was convenient random sampling. The study was conducted using self-administered questionnaire surveys to avoid any respondent biases and/or errors. The study's findings show that construction procurement is partially associated with green logistic services management, which thoroughly determines the sustainable economic development goals (SDGs). Furthermore, construction procurement is found to have a significant impact on green innovation practices that partially predict the SDGs and the mediation of green logistic services and innovation practices are partially mediated to the construction procurement and sustainable goals. In the future, the study results will help the construction practitioners, contractors, bidders, and engineering community to shape their relationships in a greener way up or down the stream of their supply chains. Additionally, the implication of green procurement and logistic services offers many challenges in the long run for attaining SDGs; however, in the short run, it gives operational efficiency and less hazardous environmental emissions.